Biomechanical Posture Assessment of Salted Fish Industry Workers in West Aceh. Issue 1 (September 2020) - Husni,; Hasanuddin, I; Hadi, K; Akram,; Firsa, T
Abstract: Salted fish is dried fish that is preserved by adding salt as the preservative medium. The process of production starts with cleaning, salting, boiling, drying, sorting, and packing. The length and complexity of the process lead to an increase in the risk of MSDs and posture complaints among the workers. This study aimed to find out the factors that caused the complaints with the biomechanical posture method. Six subjects were measured for the tension at erector spinae and the moment at (lumbar 5 sacrum 1) L5-S1 vertebral joint created by body segments and load, the calculation of the workers' body segment weight, the distance of the body's center point to the lumbar 5 sacrum 1 (L5-S1), and biomechanics at L5-S1. The largest body segment weight was found at the cleaning station, which dealt with the process of manually lifting the fish, with a bodyweight value of 70 kg, Wtrunk : 350 N, Whead : 58.8 N, Warm : 35.7 N and Wload : 300 N. The farthest distance from the body's center point to L5-S1 was found at the drying station, which deals with the process of drying the fish, with values of the distance of head (dhead ): 54.78 cm, distance of trunk (dtrunk ): 59.26 cm, distance of arm (darm ): 67.39 cm and distance of box (dbox ): 86.11 cm. The largest moment in force on L5-S1 was found at the packing station, which deals with the fish transferring and packaging process, with the value of the moment of force at 5351.86 N and 4215.28 N. Therefore, it is suggested that the salt fish industry finds solutions, re-designing the work station, decreasing the lifting load, and producing proper equipment to assist workers during labor to improve their safety and health.